Isoconversional kinetics and characteristics of combustion on hydrothermally treated biomass. (December 2017) - Ma, Peiyong; Yang, Jing; Xing, Xianjun; Weihrich, Sebastian; Fan, Fangyu; Zhang, Xianwen
Abstract: Pine sawdust and its resulting hydrochars hydrothermally produced at different time were characterized by scanning electron microscope and Fourier transform infrared spectroscopy to indicate the transformation in their morphologies and chemical structure, respectively. Afterwards, a comparative study in relation to the thermal behavior and combustion characteristics for the pine sawdust and the hydrochars was investigated. The relationship between the activation energy and various conversion rates of pine sawdust and hydrochars heated at various heating rates of 10, 20 and 30 °C/min were evaluated by the methods of Kissenger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO). The results obtained from the two methods revealed that the activation energies of hydrochars fluctuate within a narrow range when the conversion rate is 0–0.55 and then decrease drastically at the conversion rate range of 0.55–0.95, due to the decomposition of relative reactive compounds. In comparison of the two methods, the average activation energies of hydrochars obtained at 6 h and 12 h using FWO method are 112.63 and 82.83 kJ/mol, respectively, larger than 107.70 and 76.30 kJ/mol using KAS method. Highlights: Hydrochars were hydrothermally produced from pine wood sawdust. TGA analysis and chemical characterization of pine wood sawdust and its hydrochars. Activation energy variation based on two isoconversional methods was compared. The average activation energy of hydrochar produced in long time was the lowest.